Vitamin C intake and multiple health outcomes: an umbrella review of systematic reviews and meta-analyses. (4th July 2022) - Xu, Kedi; Peng, Rui; Zou, Yuanlin; Jiang, Xiaoru; Sun, Qiuyu; Song, Chunhua
Abstract: The purpose of this article was to assess the existing systematic reviews and meta-analyses for the association between vitamin C intake and multiple health outcomes. A total of 76 meta-analyses (51 papers) of randomised controlled trials and observational studies with 63 unique health outcomes were identified. Dose–response analysis showed that vitamin C intake was associated with reduced risk of all-cause mortality, cardiovascular disease (CVD), oesophageal cancer, gastric cancer, cervical cancer and lung cancer with an increment of 50–100 mg per day. Beneficial associations were also identified for respiratory, neurological, ophthalmologic, musculoskeletal, renal and dental outcomes. Harmful associations were found for breast cancer and kidney stones for vitamin C supplement intake. The benefits of vitamin C intake outweigh the disadvantages for a range of health outcomes. However, the recommendation of vitamin C supplements needs to be cautious. More prospective studies and well-designed randomised controlled trials (RCTs) are needed.